ONLINE SELF-REGULATED LEARNING STRATEGIES AMID A GLOBAL PANDEMIC: INSIGHTS FROM INDONESIAN UNIVERSITY STUDENTS (Malaysian Journal of Learning and Instruction, 2021)
Purpose – At the beginning of 2020, the COVID-19 pandemic affected many aspects of life, including education. In response, the Indonesian government mandated all educational institutions, including universities, to implement online learning. Through online learning, many university students experienced considerable changes in the way they regulated their knowledge-seeking process. This research examined the level of EFL university students' self-regulated learning during their online learning activities for an English academic writing course, as well as the difficulties encountered and strategies developed in the online learning context.  Methodology – This research employed a convergent mixed-method research design by adapting the Online Self-Regulated Learning Questionnaire (Barnard et al., 2009) and an open-ended questionnaire to discover the students' difficulties and strategies during online learning. The study involved 307 students of the English 3 (Academic Writing) course at President University, Indonesia. Descriptive statistics were employed to analyse the quantitative data sets, while the qualitative data sets were systematically coded and thematically analysed. Findings – The statistical analysis indicated that the students had a medium level of self-regulated learning skills. The qualitative analysis revealed that in the context of online self-regulated learning, the issues they faced included technical, material, time management, study space, and motivation issues. At the same time, the students attempted to alleviate these issues by improving collaboration and time management, and adopting technical, academic, and affective strategies. Significance – By exploring the level of students' self-regulated learning skills, this study provides insights for universities and lecturers into students’ ability to regulate their learning in an online learning context. Additionally, this study has identified the difficulties students face in the online learning process and their strategies to overcome these issues, which can practically inform educational institutions about the necessary support that should be provided to facilitate students' self-regulated learning skills in the online learning context.